2009
DOI: 10.1002/jmri.21699
|View full text |Cite
|
Sign up to set email alerts
|

Accurate segmentation of subcutaneous and intermuscular adipose tissue from MR images of the thigh

Abstract: Purpose: To describe and evaluate a computer-assisted method for assessing the quantity and distribution of adipose tissue in thigh by magnetic resonance imaging (MRI). Materials and Methods:Twenty obese subjects were imaged on a Philips Achieva 1.5T scanner by a fast spin-echo (FSE) sequence. A total of 636 images were acquired and analyzed by custom-made software. Thigh subcutaneous adipose tissue (SAT) and bone were identified by fuzzy clustering segmentation and an active contour algorithm. Muscle and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 26 publications
2
97
1
1
Order By: Relevance
“…More recently introduced semi-automated and automated segmentation techniques have made this process faster (13)(14)(15)(16)(17)and there is increasing evidence of good reliability and correlation with the laborious standard of manual segmentation (18). Variances of up to 1% for semiautomated segmentation of superficial fat, and 1-2% for intramuscular adipose tissue (19) have been reported and test-retest reliability appears to be excellent with a study of visceral and subcutaneous adipose tissue in children using a fully automated process demonstrating correlation coefficients of r=0.977 for VAT and r=0.999 for subcutaneous adipose tissue (SAT) (20).…”
Section: Authorsmentioning
confidence: 99%
“…More recently introduced semi-automated and automated segmentation techniques have made this process faster (13)(14)(15)(16)(17)and there is increasing evidence of good reliability and correlation with the laborious standard of manual segmentation (18). Variances of up to 1% for semiautomated segmentation of superficial fat, and 1-2% for intramuscular adipose tissue (19) have been reported and test-retest reliability appears to be excellent with a study of visceral and subcutaneous adipose tissue in children using a fully automated process demonstrating correlation coefficients of r=0.977 for VAT and r=0.999 for subcutaneous adipose tissue (SAT) (20).…”
Section: Authorsmentioning
confidence: 99%
“…The origin of the localization system was determined as the bone gravity center on the basis of an automatic segmentation of bone, muscle and subcutaneous adipose tissue. The automatic segmentation has been developed in C+ + using OpenCV library as previously published by Positano et al 50 in order to obtain a fast and fully automatic segmentation. While Positano et al used a gradient vector flow snake algorithm 51 , we used a more classical polygonal active contour algorithm 52 which determines the boundary between the subcutaneous fat and muscle tissues.…”
Section: T 2 Mappingmentioning
confidence: 99%
“…In fuzzy logic, each pixel is assigned a fuzzy membership to indicate the probability that the pixel is fat. Then the fat is extracted by minimizing the membership function instead of being based solely on a threshold (Positano et al, 2004;Positano et al, 2009). More mathematically complex models have been created to compensate for the inhomogeneities in the intensity images (Hou, 2006;Vovk et al, 2007).…”
Section: Automatic Measurementmentioning
confidence: 99%
“…In order to separate the visceral and subcutaneous fat, curve deformation methods (Positano et al, 2004;Positano et al, 2009;Zhao et al, 2006) have also been reported. These methods deform a curve inwards from skin contour to locate a muscle layer.…”
Section: Automatic Measurementmentioning
confidence: 99%
See 1 more Smart Citation